2020
DOI: 10.1021/jacs.0c10133
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity, Formation, and Solubility of Polyoxometalates Probed by Calorimetry

Abstract: Room temperature calorimetry methods were developed to describe the energy landscapes of six polyoxometalates (POMs), Li-U24, Li-U28, K-U28, Li/K-U60, Mo132, and Mo154, in terms of three components: enthalpy of dissolution (ΔHdiss), enthalpy of formation of aqueous POMs (ΔHf,(aq)), and enthalpy of formation of POM crystals (ΔHf,(c)). ΔHdiss is controlled by a combination of cation solvation enthalpy and the favorability of cation interactions with binding sites on the POM. In the case of the four uranyl peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 52 publications
2
35
0
Order By: Relevance
“…In the current study we determined Δ H diss , Δ H f ° (aq) , and Δ H f ° (c) values for the uranyl lithium triperoxide monomer (Li−UT) and four UPCs (LiRb−U@U 24 , LiNa−U 24 Pp 12 , NaK−U 24 Pp 12 , and U 60 Ox 30 ; Pp=pyrophosphate, Ox=oxalate; see Figure 1 and Table 1). This study reveals how the energy landscape of previously measured topologies (U 24 and U 60 ) [13a] is impacted by counter cations and the substitution of pyrophosphate and oxalate for hydroxo bridges. Additionally, the enthalpy results for Li−UT allow us to calculate the enthalpy of reaction for the formation of Li−U 24 and Li−U 28 from their monomeric building blocks.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…In the current study we determined Δ H diss , Δ H f ° (aq) , and Δ H f ° (c) values for the uranyl lithium triperoxide monomer (Li−UT) and four UPCs (LiRb−U@U 24 , LiNa−U 24 Pp 12 , NaK−U 24 Pp 12 , and U 60 Ox 30 ; Pp=pyrophosphate, Ox=oxalate; see Figure 1 and Table 1). This study reveals how the energy landscape of previously measured topologies (U 24 and U 60 ) [13a] is impacted by counter cations and the substitution of pyrophosphate and oxalate for hydroxo bridges. Additionally, the enthalpy results for Li−UT allow us to calculate the enthalpy of reaction for the formation of Li−U 24 and Li−U 28 from their monomeric building blocks.…”
Section: Introductionmentioning
confidence: 79%
“…The derived positive Δ H diss values measured for UPCs revealed that their dissolution process is entropically driven and determined Δ H f ° (aq) values indicate that hydroxo bridges stabilize cluster topologies in comparison to those containing only peroxo bridges. The enthalpy of reaction (Δ H rxn ) for the conversion of Li−U 28(aq) to Li−U 24(aq) , previously described in the literature, [12] was found to be favorable and thus Li−U 28 is kinetically favored whilst Li−U 24 is thermodynamically favorable [13a] …”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Inspired by the observation and a thorough search of previous literatures, [11] we tested different threads, including cotton, plastic, and copper, and discovered a general method to produce Cs 4 PbBr 6 crystals using threads as seeds. The crystal growth process was investigated by calorimetry and real-time scanning electron microscopy (SEM), [12] which showed that the growth of Cs 4 PbBr 6 in solution is an exothermic enthalpy driving process, and the surface energy calculations further supported the formation of rhombohedra shape. [7a,13] In this work, the obtained microcrystals show strong green luminescence with an absolute PL quantum yield (PLQY) of 31.5%, which was used to fabricate high-performance white and green LEDs.…”
Section: Introductionmentioning
confidence: 99%